Study on Creating a Simplified Model of Quality Management System in a SME from the Central Region of Romania. (2016) - Pop, Liviu Dorin
Abstract: Quality management system (QMS) implementation and certification, especially for small and medium enterprises, involves, sometimes quite large volume of documents and records relating to the number and duties of the employees. The paper deals with efficient organizational and monitoring solutions, focusing on document management, which could improve the system. Thus, the case study is focused on a small size company from the automotive sector, whose QMS is certified according to ISO 9001, aiming at two aspects: reducing the number of QMS specific procedures and presenting a software solution.